The Influence of the Anomalous Coupling on the in the Randall - Sundrum Model - Thi Ha Giang, Bui (VNU Journal of Science: Mathematics - Physics; Vol 40 No 4DO - 10.25073/2588-1124/vnumap.4962, 2024)
A study to produce a Z boson and a radion through anomalous couplings is considered from muon-muon colliders at the center of mass energy 10 TeV. The leptonic decays of the Z boson and a radion decaying into a pair of photons are considered. The integrated luminosity of muon colliders is 10 . The production cross-sections depend on the polarization of  initial beams, the center of mass energy . The minimum integrated luminosity value is shown to correspond to a significance larger than 5s.